(x+6)+(x+2)=0

Simple and best practice solution for (x+6)+(x+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+6)+(x+2)=0 equation:



(x+6)+(x+2)=0
We get rid of parentheses
x+x+6+2=0
We add all the numbers together, and all the variables
2x+8=0
We move all terms containing x to the left, all other terms to the right
2x=-8
x=-8/2
x=-4

You can always share this solution

See similar equations:

| y-0,8y=200 | | 28,8-(x-17,6)=5,4 | | 12q=200-2q | | 200-2q=20+4q | | 7(3x-x)=2 | | 9^(2x+1)=27 | | 3a+1/2a=6 | | 7n-3=4n+ | | 24-2q=24-4q | | 3(x-7)=24-2x | | 6n+8=2n+6 | | 6a^2-12a+1=0 | | 2x2+11x+10=0 | | (110/x)(12x)=1880 | | -2(5r+4)=-(r-10) | | 7n+3=3n+227 | | 8(3w+7)/5=1 | | 2(x?9)?2???32=0 | | (2x^2-1)^2=16 | | 3y-(y+4)=4y-8 | | 1000=1.8(10^2x) | | 85+5x=100 | | 7n-13=71 | | 9n-4=5 | | -22-6x=-4x+10 | | 3-9y=5y | | 3x–7=x+3 | | 6. 3x–7=x+3 | | 9-3y=5y | | 9x÷8+6=3x÷6+2 | | -11-x=x+5 | | u/8=6u= |

Equations solver categories